The Implementation of Multisensory Technique for Children with Dyslexia - Agus Supriatna; Ediyanto Ediyanto (The Center for Disability Studies and Services Brawijaya University, 2021)
Children with learning disabilities are a children's physiological or biological condition in which the competence or achievement is not according to predetermined standard criteria—learning disabilities in the form of errors in reading called dyslexia. Children with specific learning difficulties dyslexia experience difficulties in academic aspects; therefore, it is necessary to carry out an academic assessment and material for tutors to improve dyslexia reading skills. The multisensory technique is alternatives that used as reference material for tutors to improve dyslexia reading skills. Multisensory Techniques that can be used include 1) Reading and Spelling Training; 2) Visual Technique; 3) Auditory Technique, and 4) Tactile Technique. The reading and spelling focus on maintaining relationships between sounds and symbols starts with a single letter and continues with consonant combinations, vowel continuation, and complex letter groupings. The Visual Technique can start by using a picture card with the word written on the bottom (flashcard). Auditory technique for children who have difficulty with sound problems, teach a pair of short words and ask the child to say which word is correct. In addition, children with dyslexia will have the best learning by touch, so it is essential to incorporate this learning style into the instruction as a tactile technique.